PENGARUH MODEL GAME-BASED LEARNING BERBANTUAN WAYGROUND AI TERHADAP PENINGKATAN PEMAHAMAN KOSAKATA BAHASA INGGRIS SISWA KELAS IV DI SDN PARSANGA I - Endang Agus Sulasmi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The problems faced in English language learning at SDN Parsanga I are the students' low vocabulary mastery, caused by a lack of interactive learning media and the use of monotonous methods. Students have difficulty understanding and remembering vocabulary, as well as using it in the correct sentence context. This study aims to determine the effect of Game-Based Learning assisted by Wayground AI on the English vocabulary comprehension of fourth-grade students at SDN Parsanga I. This study uses a quantitative approach with a one-group pretest-posttest design, where students are given a pretest and posttest after the implementation of Wayground AI as a game-based learning medium. The research results show a significant improvement in vocabulary comprehension, with an average pretest score of 67.71 and a posttest score of 82.29. The paired sample t-test analysis shows a Sig. (2-tailed) value < 0.001, indicating a significant effect of using Wayground AI. The R Square test result of 0.611 indicates that 61.1% of the vocabulary comprehension improvement can be explained by this model. Additionally, the N-Gain results show an average increase of 0.45 or 45% (moderate category). This research suggests optimizing the use of technology in learning and providing continuous training for teachers. Keywords: Game-Based Learning, Wayground AI, Vocabulary Comprehension, English Language Learning, Elementary School.